1986
DOI: 10.1159/000124459
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia Alters the Frequency and Amplitude of Pulsatile Luteinizing Hormone Secretion in the Ovariectomized Rat

Abstract: Studies were undertaken to (1) examine the effects of hyperprolactinemia on the frequency and amplitude of pulses of LH, and (2) determine if changes in pituitary sensitivity to LHRH were involved in the prolactin-induced suppression of LH secretion. Rats were bilaterally ovariectomized (day 0). Ovine prolactin (4 mg/kg body weight, subcutaneously) or vehicle was administered every 8 h beginning at 09.00 h on day 4 after ovariectomy and continuing until 09.00 h on day 6. On day 6, between 07.00 and 09.00 h all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 23 publications
6
44
0
Order By: Relevance
“…Secretion of PRL has been reported to inhibit LH secretion in several species [24], especially in rats and humans [25,26]. The combined effect of PRL and dopamine inhibits LH, but PRL alone does not.…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of PRL has been reported to inhibit LH secretion in several species [24], especially in rats and humans [25,26]. The combined effect of PRL and dopamine inhibits LH, but PRL alone does not.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mRNA for PRL-R has been detected in the brain using both RT-PCR (Chiu et al 1992, Sugiyama et al 1994, Pi & Grattan 1998b, 1999b and in situ hybridization (Chiu & Wise 1994, Bakowska & Morrell 1997, Mann & Bridges 2002. Prolactin has been implicated in the regulation of a variety of brain functions, including the suppression of adrenocorticotrophin secretion during the stress response (Torner et al 2001), an increase in feeding and appetite (Sauve & Woodside 1996, 2000, and the suppression of fertility (Cohen-Becker et al 1986), as well as the well-characterized short-loop negative feedback regulation of its own secretion by stimulating tuberoinfundibular dopamine (TIDA) neuronal activity (Freeman et al 2000). In addition, prolactin is known to be involved in further brain functions during lactation, such as the release of oxytocin for the milk ejection reflex (Parker et al 1991, Ghosh & Sladek 1995 and induction of maternal behaviour (Bridges 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It has been thought that the N surge of PRL is essential for maintaining PSP and is stored in the hypo thalamus as memory for 6 days [4, 71. Gorospe and Freeman [10] have reported that at the end of PSP, estradiol plays an important role for terminating PSP in the condition of proge sterone to be decreased.Generally, a reverse relationship is observ ed between the secretion of gonadotropins and PRL in reproductive phenomenon [2,14], such as PSP, pregnancy and lactation, where PRL is secreted dominantly, whereas luteinizing hormone (LH) and follicle stimulating hormone (FSH) remain a basale level [2,19, 201. In these stage PRL probably stimulates progesterone secretion from the copora lutea, and proges terone suppresses the secretions of LH and FSH through the hypothalamus and/or pituitary.…”
mentioning
confidence: 99%
“…Generally, a reverse relationship is observ ed between the secretion of gonadotropins and PRL in reproductive phenomenon [2,14], such as PSP, pregnancy and lactation, where PRL is secreted dominantly, whereas luteinizing hormone (LH) and follicle stimulating hormone (FSH) remain a basale level [2,19, 201. In these stage PRL probably stimulates progesterone secretion from the copora lutea, and proges terone suppresses the secretions of LH and FSH through the hypothalamus and/or pituitary.…”
mentioning
confidence: 99%